Managing Oracle Fusion applications [ - Bingham, Richard [ (Richard John)] (McGraw-Hill, 2011)
"From Oracle Press--expert techniques for effectively managing Oracle Fusion Applications. Managing Oracle Fusion Applications explains how to use a comprehensive range of tools, services, and worked best practices, organized into an easy-to-use and practical toolbox, to manage Oracle Fusion Applications--the integrated suite of next-generation enterprise applications that combine the best capabilities from Oracle's extensive product portfolio. Written by a member of the Oracle team designing the support strategy for Oracle Fusion Applications, this is the first and only book on the topic. Effective system management increases application up-time, improves performance, and lowers the total cost of ownership. This Oracle Press guide demonstrates how to achieve these goals.Complete coverage of Oracle Fusion Applications management: Oracle Fusion Applications Product Overview; Oracle Fusion Applications Technical Overview; Successful Enterprise Application Management; Oracle Fusion Applications Lifecycle; Oracle Fusion Applications Management Toolbox; Reliability Management Toolbox; Availability Management Toolbox; Performance Management Toolbox; Optimization Management Toolbox; Governance Management Toolbox; Planning for the Future"-- Provided by publisher